CHILDREN’S ACQUISITION OF INFORMATION QUESTION - CITRA ANGGIA PUTRI; FARIDA HANIM SARAGIH (FIP Unimed, 2014)
The main objective of this article was to discover the children’s information questions. The instrument used were observations of the children use of information questions and interview sessions with their parents. The subjects were three children of two years old, two females and one male. A qualitative research was applied. The result of the findings shows that the three children were able to use the information questions in Bahasa Indonesia but (what) was first commonly used by them and they functioned as question for asking about something for the children’s use of information questions, their developments seem to be very much concerned with the influence of the people around them. Thus, special care and attention should be given to children. Their language developments very much influenced by the people around them. This article implies that in the process of language acquisition, parent(s) should give special attention so that the children’s skill in using information questions would be more focused and developed in accordance with the children’s development. Keywords : Language acquisition, information question, and interview session